Układ różniczkowy - Dniestrzański, Piotr (Differential sequence, 2007)
In the paper the author presents the most important properties of the differential sequence. It is the sequence of { / } where/„(*) = (arc tgx)<n); n = 1, 2, .... This sequence is linearly independent in L2(R) and it is the linearly dense subset at L2(R) space. Moreover, in some cases, functions { f } are useful in approximation problems. The author discuses connections between the differentia sequence and other orthogonal sequences. The function y = arctgx is called differential wavelet.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 168-175